Design and Optimization of a Novel Spectrophotometric Method using Response Surface Methodology for the Determination of Los artan Potassium in Pharmaceuticals - Demirkaya-Miloglu, Fatma; Polatdemir, Elmas; Senol, Onur; Kadioglu, Yucel (Current Pharmaceutical Analysis, 2017)
Backround: A new spectrophotometric method based on the oxidation reaction between iodide and iodate in the presence of the carboxylic acid form of losartan potassium (LP) was developed for the estimation of LP in pharmaceutical products. Method and Results: HPLC/MS, kinetic studies and central composite design were used for the formation reactions, equilibration, and determination of stability duration and experimental conditions, respectively. The developed spectrophotometric method was validated. As such, the equilibration period was calculated to be 10 min and 9.7 mmol/L KI and 0.59 mmol/L KIO3 were utilized. The optimal temperature was 32.3 °C. The method was determined to be linear between 4-30 µg/mL with a correlation coefficient of 0.9996. The limit of detection and limit of quantification were calculated to be 0.55 and 1.85 µg/mL, respectively. Pharmaceutical preparations were analyzed by the developed kinetic spectrophotometric method. The obtained results ranged between 94.9 % and 100.9 %. Conclusion: According to our results the developed method can be used as an alternative for the simple and routine determination of LP in industrial quality control laboratories. Moreover, this proposed method use experimental design which the optimized reaction conditions to be determined with a minimal number of experiments.
Keywords: losartan potassium